Eu aos olhos dos outros: aceitação do corpo pelos outros, vinculação e ansiedade em pacientes com cancro da mama - Mariana Martins Meireles (2021)
Body Acceptance by Others (ACPO) is defined as the perception that we have about how others accept our bodies. This variable is of special interest when it comes to breast cancer since the changes resulting from the treatment are often substantial, visible and involve a part of the body linked to femininity. The attachment dimensions and anxiety are two variable that can influence ACPO because they may be associated with ineffective coping styles to deal with bodily changes, but also, with regards to attachment, because it provides the individual with a frame of reference for himself and others. This study intended to explore the differences in ACPO, attachment and anxiety between a group of women with breast cancer and a group of healthy women, and explore the relationship between ACPO, attachment and anxiety in women with breast cancer. 130 cancer patients and 140 healthy women participated in the study. The participants completed self-reported measures to assess ACPO (Body Acceptance by Others Scale), anxiety (Escala de Ansiedade Depressão e Stress) and the different dimensions of attachment (Escala de Vinculação do Adulto). The results show that the groups did not differed in terms of ACPO nor in any dimensions of attachment but did differ in terms of anxiety with the clinical group exhibiting higher values than the control group. The results also show a negative correlation between ACPO and anxiety, a negative correlation between ACPO and the anxious dimension of attachment and a positive correlation between ACPO and the dimensions of comfort in the proximity and trust in others of attachment. The linear regression model indicates that the coordinated effect of attachment dimensions and anxiety explain 24% of variability of ACPO, with comfort in proximity proving to be a significant predictor of ACPO. This study results suggest that attachment and anxiety have an important role on ACPO in women with breast cancer being that becomes fundamental for future investigations to continue focusing on these variables and invest in more integrative and holistic interventions that take in account the attachment system of the patient and the role of anxiety in his body image.